EFEK REWARD TERHADAP MOTIVASI KERJA PEGAWAI DI KANTOR DINAS KESEHATAN KABUPATEN SUMBAWA - Sarita, Maulinda; Pamungkas, Binar Dwiyanto (Fakultas Ekonomi dan Manajemen, 2024)
This study aims to determine the effect of rewards on employee work motivation at the Health Office of Sumbawa District. The type of this study was associative study used to examine the significance effect of rewards on employee work motivation at the Health Office of Sumbawa District. The type of data used in this study was quantitative data obtained directly through questionnaires distributed to research respondents, namely all employees at the Health Office of Sumbawa District. The number of respondents in this study was 84 people who were determined using the Slovin formula and selected using probability sampling techniques with the simple random sampling method. The all of data were analyzed using simple linear regression analysis techniques, partial hypothesis testing (t test), and determinant coefficient test (R2. The results of this study showed that the rewards had a positive and significant effect on employee work motivation at the Health Office of Sumbawa District. The total effect of rewards on employee work motivation at the Health Office of Sumbawa District was 30.9%, while the remaining of 69.1% was effected by other factors not examined in this study, such as leadership style, work discipline and job satisfaction.